Non-coding RNAs are involved in tumor cell death and affect tumorigenesis, progression, and treatment: a systematic review - Han, Zeping; Luo, Wenfeng; Shen, Jian; Xie, Fangmei; Luo, Jinggen; Yang, Xiang; Pang, Ting; Lv, Yubing; Li, Yuguang; Tang, Xingkui; He, Jinhua (Frontiers in Cell and Developmental Biology, 2024)
Cell death is ubiquitous during development and throughout life and is a genetically determined active and ordered process that plays a crucial role in regulating homeostasis. Cell death includes regulated cell death and non-programmed cell death, and the common types of regulatory cell death are necrosis, apoptosis, necroptosis,autophagy, ferroptosis, and pyroptosis. Apoptosis,Necrosis and necroptosis are more common than autophagy, ferroptosis and pyroptosis among cell death. Non-coding RNAs are regulatory RNA molecules that do not encode proteins and include mainly microRNAs, long non-coding RNAs, and circular RNAs. Non-coding RNAs can act as oncogenes and tumor suppressor genes, with significant effects on tumor occurrence and development, and they can also regulate tumor cell autophagy, ferroptosis, and pyroptosis at the transcriptional or post-transcriptional level. This paper reviews the recent research progress on the effects of the non-coding RNAs involved in autophagy, ferroptosis, and pyroptosis on tumorigenesis, tumor development, and treatment, and looks forward to the future direction of this field, which will help to elucidate the molecular mechanisms of tumorigenesis and tumor development, as well as provide a new vision for the treatment of tumors.